2011
DOI: 10.2320/matertrans.mb201004
|View full text |Cite
|
Sign up to set email alerts
|

Interface Structure of Gold Particles on TiO<SUB>2</SUB> Anatase

Abstract: Gold particles supported on titanium dioxide (TiO 2 ) are known to activate many catalytic reactions. In this study, interface structure of gold on anatase was examined in the case on an anatase {101} surface, since the surface is the most important for several photocatalytic reactions. Anatase TiO 2 nanorods having clear washboard-like {101} outer surfaces were synthesized by using a double surfactants system. From high resolution electron microscopy observation for gold particle on the {101} surface, the (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…They also showed that the generation of the catalytically active Au sites does not correlate with the nominal charge on Au, and that the defect sites in TiO 2 surface play an important role not only in anchoring clusters, but also in generating catalytic activity on the clusters. Isoda and coworkers also investigated the interface structure of gold NP on anatase TiO 2 by TEM observation and showed that the (1 1 3) plane of gold NP was found to be parallel to the (1 0 1) surface of anatase TiO 2 [23]. This result suggests that the smallest lattice mismatching between Au NP and the support was one of the important factors for generating a hetero-junction between them.…”
Section: Characteristics Structures Of Gold Np Catalystsmentioning
confidence: 85%
“…They also showed that the generation of the catalytically active Au sites does not correlate with the nominal charge on Au, and that the defect sites in TiO 2 surface play an important role not only in anchoring clusters, but also in generating catalytic activity on the clusters. Isoda and coworkers also investigated the interface structure of gold NP on anatase TiO 2 by TEM observation and showed that the (1 1 3) plane of gold NP was found to be parallel to the (1 0 1) surface of anatase TiO 2 [23]. This result suggests that the smallest lattice mismatching between Au NP and the support was one of the important factors for generating a hetero-junction between them.…”
Section: Characteristics Structures Of Gold Np Catalystsmentioning
confidence: 85%
“…Since the (112) plane of anatase is also at an angle of 52° from the (100) anatase plane, the (112), and (111) crystal planes of gold and anatase, respectively, are most likely to be parallel and a planar heteroepitaxial interface is indicated. While coherent heterointerfaces between gold nanoparticles and anatase nanostructures remain uncommon, the heteroepitaxy of Au on TiO 2 has been reported in a handful of reports. …”
Section: Results and Discussionmentioning
confidence: 99%